2021
DOI: 10.1109/jiot.2020.3034024
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative Body Temperature Measurement Solution: Combination of a Highly Accurate Monitoring System and a Visualized Public Health Cloud Platform

Abstract: To quickly isolate suspected cases to control the epidemics, this study proposes a body temperature monitoring system with a thermography based on the Internet of Things (IoT) architecture. The collected data are transmitted to a back-end platform via wireless communication. Using the analyzed data, the platform provides services, such as instant alerts for any anomalies, infectious disease outbreak prediction, and risk level assessment for a given area, and it will be a great help to epidemic prevention. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…At present, the research on mobile medical service systems based on cloud platforms is still relatively few and is in its infancy. Through the cloud platform, it can complete the storage, calculation, and screening of relevant data in the medical system, provide the management of patients' daily health records, and complete the medical care of patients in a more real-time and effective manner [ 22 ]. After users complete the measurement of physical indicators, they store the health indicator data on the cloud platform and read it selectively at any time through the mobile terminal device.…”
Section: Related Workmentioning
confidence: 99%
“…At present, the research on mobile medical service systems based on cloud platforms is still relatively few and is in its infancy. Through the cloud platform, it can complete the storage, calculation, and screening of relevant data in the medical system, provide the management of patients' daily health records, and complete the medical care of patients in a more real-time and effective manner [ 22 ]. After users complete the measurement of physical indicators, they store the health indicator data on the cloud platform and read it selectively at any time through the mobile terminal device.…”
Section: Related Workmentioning
confidence: 99%
“…In their study, Jiang et al [22] suggested the need for isolating suspected cases in order to control epidemics. To achieve this, they proposed an IoT-based architecture that includes a body temperature monitoring device with thermography.…”
Section: Inertial Sensor Yes Yesmentioning
confidence: 99%
“…The front-end network and back-end network each have two switches, and the two switches at the same end form the active standby relationship. The HSRP protocol is used to ensure the active/standby working relationship in a normal environment and complete the active/standby switching when necessary [17][18].…”
Section: Network Monitoring Management Systemmentioning
confidence: 99%